"Estudio de factibilidad para la creación de un centro de amaestramiento y domesticación para mascotas en el Cantón Quevedo año 2014" - Plaza Barahona, Alán Paúl (2014)
This "Feasibility Study for the creation of a master key and domesticated pet in the canton Quevedo collecting information from secondary sources supported theoretically understood; then the market study is analyzed to determine the unmet need for this service, just as it was learned that there is no such venture in the city of Quevedo; with the analysis of the technical study is able to locate strategically THE place where the local is set, also the organizational structure was established according to the existing need Immediately the economic study was done through economic techniques - financial, yielding positive results: 11,689 IRR NPV 24.98%, cost-benefit ratio capital recovery $ 1.26 3 years